Safety Requirements Identification in Suborbital Payload Experiments - Heuller Aloys Carneiro Procópio; Luiz Eduardo Galvão Martins; Carlos Henrique Netto Lahoz (Journal of Aerospace Technology and Management)
In the concept, design, and development phases of suborbital payload scientific experiments, designers tend to focus on what will be tested using automation and procedures that support the vehicle and space environment. Although tests are the focus, safety is one of the primary areas that may contribute to a successful mission. This paper presents the typical Brazilian suborbital payloads and rockets, and then reviews some losses during the launching campaigns. The system-theoretic process analysis (STPA), which is based on the system-theoretic accident model and process (STAMP) approach, was used to identify 32 unsafe control actions (UCAs), 77 loss scenarios, and 28 safety constraints. These safety constraints were the basis for establishing 74 safety requirements modeled in systems modeling language (SysML). A group of experts in space systems evaluated these safety requirements, and a case study was performed to test the requirement set. The results may contribute to mitigating or eliminating hazards related to these space systems and launch mission safety.